The Spirituality of Islamic Beauty - Philips, Gerardette (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Anyone with the knowledge of Islamic culture knows that Islam has produced works of art and incredible architecture - Persian miniatures, the Taj Mahal, mosque, music etc. However, only a few people realize that this rich artistic heritage is rooted in a world view that underlines love and beauty. The relationship between love and beauty is quite clear. We love what we find beautiful. This article offers the meaning of beauty in Islam from the perspective of spirituality as seen in the Quran, Calligraphy, Arabesque, music, mosque, Mihrab, The Alchemy of Light, and finally the concrete expression of this beauty in the life of the human soul. The Prophet said, “God is beautiful and loves beauty.” In understanding the beauty and love in Tawhid, the Oneness of God – “There is no god but Allah,” the hope is that this paper will enable one to know the All Beautiful One - God in various manifestations. If God is beautiful, then nothing is truly beautiful but God. And if God is loving, then nothing really loves besides Allah.